Isolation of a Soluble Resistance-Enhancing Factor from Mycobacterium phlei - Fox, Alfred E. (1966)
Fox, Alfred E. (Warner-Lambert Research Institute, Morris Plains, N.J.), Joachim Anschel, George L. Evans, Raam R. Mohan, and Benjamin S. Schwartz. Isolation of a soluble resistance-enhancing factor from Mycobacterium phlei. J. Bacteriol. 92:285–290. 1966.—Extraction of a crude cell wall preparation from Mycobacterium phlei with 20% urea yielded a fraction which induced a state of enhanced resistance to microbial challenge. The resulting soluble extract, after removal of the urea, represented a 15% yield of solids with the separation of the biologically active component(s) and elimination of toxicity. Single oral or subcutaneous submicrogram doses of this material induced a prolonged state of increased resistance to subsequent challenge with Salmonella enteritidis in mice. This effect appeared as early as 2 hr after oral administration and persisted for at least 30 days. Protection against experimental infection with Staphylococcus aureus was also demonstrated. Resistance to viral challenge with influenza type A was observed after intranasal administration of the M. phlei extract to mice. The isolated material was found to contain carbohydrate, protein, nucleic acids, and lipids. The lipids represented 60% of the total solids, and were all short-chain fatty acids. No toxic effects, including pyrogenicity, could be demonstrated after oral or parenteral administration of this preparation.